2020
DOI: 10.1109/access.2020.3040506
|View full text |Cite
|
Sign up to set email alerts
|

Unstructured Text Documents Summarization With Multi-Stage Clustering

Abstract: In natural language processing, text summarization is an important application used to extract desired information by reducing large text. Existing studies use keyword-based algorithms for grouping text, which do not give the documents' actual theme. Our proposed dynamic corpus creation mechanism combines metadata with summarized extracted text. The proposed approach analyzes the mesh of multiple unstructured documents and generates a linked set of multiple weighted nodes by applying multistage Clustering. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 57 publications
(173 reference statements)
0
8
0
Order By: Relevance
“…The character is identified by examining its forms and comparing its features. A mouse-equipped framework for the perception of handwritten letters or images was proposed [18]. [19,20] presented a comparison of opinion summarization techniques and proposed an unsupervised algorithmic approach for opinion summarization that does not require annotated training data, adequately classifies the input text and achieves 96% accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The character is identified by examining its forms and comparing its features. A mouse-equipped framework for the perception of handwritten letters or images was proposed [18]. [19,20] presented a comparison of opinion summarization techniques and proposed an unsupervised algorithmic approach for opinion summarization that does not require annotated training data, adequately classifies the input text and achieves 96% accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In some cases, the individual would lose completely its position data that is not predictable due to the potential region in which it is situated. By resolving this problem, there is a need for modifying the parameters that are shown in Equation (19).…”
Section: Fisa-efo Algorithmmentioning
confidence: 99%
“…In 2020, Saeed et al 19 have examined the dynamic corpus creation model by combining extracted summarized text with metadata. The developed model has examined the interconnection of many unstructured documents.…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…The clustering algorithms take an important role in this purpose, which group together the crime reports of similar crime types. There are many clustering methods [1,2] that can be used to cluster both structured and unstructured datasets. But research on report clustering over a long period of time has shown that it is neither an easy task nor a perfect solution yet.…”
Section: Introductionmentioning
confidence: 99%